2020
DOI: 10.1007/s00228-020-02962-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety of hydroxychloroquine in COVID-19 and other diseases: a systematic review and meta-analysis of 53 randomized trials

Abstract: Introduction Many concerns still exist regarding the safety of hydroxychloroquine (HCQ) in the treatment of Coronavirus Disease 2019 (COVID-19). Objectives The purpose of this study was to evaluate the safety of HCQ in the treatment of COVID-19 and other diseases by performing a systematic review and meta-analysis. Methods Randomized controlled trials (RCTs) reporting the safety of HCQ in PubMed, Embase, and Cochrane Library were retrieved st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 118 publications
(241 reference statements)
1
16
0
Order By: Relevance
“…Results are coherent with a previous evidence synthesis collecting data only from RCTs, but not limited to COVID‐19, being focused on other settings such as rheumatological diseases characterized by different HCQ schedules and including fewer studies in the framework of treatment or prevention of SARS‐CoV‐2 infection 12 …”
Section: Discussionsupporting
confidence: 87%
“…Results are coherent with a previous evidence synthesis collecting data only from RCTs, but not limited to COVID‐19, being focused on other settings such as rheumatological diseases characterized by different HCQ schedules and including fewer studies in the framework of treatment or prevention of SARS‐CoV‐2 infection 12 …”
Section: Discussionsupporting
confidence: 87%
“…Many concerns exist regarding the safety of hydroxychloroquine in the treatment of COVID-19. 4 Treatment for HF individuals with COVID-19 included best practices for supportive management of acute hypoxic respiratory failure, haemodynamics, organ failures, and general clinical status. Eight patients progressed to SARS requiring invasive pulmonary mechanical ventilation, seven needed non-invasive pulmonary ventilation, and one patient received supplemental oxygen by catheter.…”
Section: Resultsmentioning
confidence: 99%
“…hydroxychloroquine, chloroquine, clarithromycin, azithromycin, antiviral therapy, convalescent plasma, and immunomodulatory agents). Many concerns exist regarding the safety of hydroxychloroquine in the treatment of COVID‐19 4 . Treatment for HF individuals with COVID‐19 included best practices for supportive management of acute hypoxic respiratory failure, haemodynamics, organ failures, and general clinical status.…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent study at a large medical center in New York City that examined the association between hydroxychloroquine use and intubation or death of patients with Covid-19, revealed that hydroxychloroquine administration was not associated with either a greatly lowered or an increased risk of the composite end-point of intubation or death [ 99 ]. However, most recent meta-analysis studies demonstrated that hydroxychloroquine administration might cause harm in COVID-19 patients [ 100 , 101 ].…”
Section: Treatmentmentioning
confidence: 99%